“Only in My Dreams Could Happen”- A Greek Gay Man’s Experience of Intimate Relationships in a Country that Has Just Passed a Same-Sex Union Law; a Qualitative Study Using Interpretative Phenomenological Analysis - Matiaki, Maria; Giuseppe Masullo (European Journal of Multidisciplinary Studies, 2017)
This study investigated how a Greek gay man experienced his homosexuality over the course of his life, while living in Greece. Research has shown that sexuality does not play an important role in variables such as intimacy, and love (Elizur - Mintzer, 2003; Wagner, Remien - Carballo-Dieguez, 2000). Social and cultural parameters however affect sexuality acceptance and psychological wellbeing (Bader, 2009; Wight, LeBlanc - Lee Badgett, 2013). In the Greek society many gay men over the years chose to conceal their sexual identity out of fear of harassment (Veremis et al, 2013). Greece however has just passed a new same-sex union law aiming at giving equal rights to homosexual couples. This study based on a single interview case, aimed at interpreting the participant’s reality under the premises of Interpretative phenomenological analysis. The participant, a 42 year old gay man, participated in an one hour semi-structured interview. Four themes emerged as a result of the transcript analysis; the need to be normal; time as a construct in his life; the importance of micro and macro environment; dealing with feelings and emotions. The participant’s need for safety and comfort, the emotional implication from lack of it, as well as his positive emotions as a result of intimacy, love and wide acceptance have emerged from the analysis of the theme “dealing with feelings and emotions”. The findings of the analysis are supported by existing literature. The nature of this qualitative study has helped the researcher to give voice to the participant and to analyze his experiences and concerns from a psychological perspective (Larkin, Watts, - Clifton, 2006).